Risk Assessment and Control Activities in the Management of Lambo Reservoir Development Funds: SPIP-Based Evaluation - Susana Purnamasari Baso (Penerbit Hellow Pustaka, 2025)
This study evaluates the compliance of risk assessment and control activities within the Government Internal Control System (SPIP) in managing the Lambo Reservoir development funds at BWS NT II with Government Regulation No. 60 of 2008, identifies the inhibiting factors, and formulates improvement strategies. Using a qualitative approach through interviews and observations with employees and affected communities, supported by project documents, financial reports, news sources, and regulations, the study assesses five SPIP components: control environment, risk assessment, control activities, information communication, and monitoring. The results show that SPIP implementation is not yet optimal, particularly in the absence of comprehensive risk mapping—such as risks of delayed payments, land disputes/validity issues, and potential fund misuse along with inconsistent application of control procedures like land document verification, segregation of duties, reconciliations, and periodic audits, as well as inadequate transparency and public outreach that contribute to distrust. Key obstacles include incomplete or outdated land data, weak inter-agency coordination, limited human and technological resources, and geographical logistical challenges. The recommended improvements include forming an integrated land validation team with the National Land Agency, digitizing documents and implementing case tracking, strengthening key controls through multi-layer verification, real-time reconciliation, and periodic risk-based audits, enhancing public outreach and complaint channels, and improving project monitoring and logistical support to provide a roadmap for strengthening SPIP effectiveness and ensuring accountable and timely project completion.